Portfolio Workbook as an Effective Method for Student-Centered Learning of Chemical Engineering Principles - Muhammad Roil Bilad; Saiful Prayogi (Universitas Pendidikan Indonesia (UPI), 2021)
Principles of Chemical Engineering (PCE) course is a core and highly important subject to study Chemical Engineering program that caters most fundamental concepts that bridge science to engineering. This study assess the effectiveness of portfolio workbook as a strategy to enhance student active learning in PCE. It was implemented for a full-semester and the student feedbacks on perceptions and implementation of the method was obtained after the course was completed. Results show that most participant agreed on the imposing mark on the workbook to enhance their study motivation. Vast majority of the students (82%) admit that the workbook significantly helped them in mastering the subject, thus recommended the method for other subjects (85%). The workbook as well as the method implementation can further be improved by providing short-answer as well as more intense scaffolding.